Predicting CMEs Using ELEvoHI With STEREO‐HI Beacon Data. Issue 12 (3rd December 2021) - Bauer, Maike; Amerstorfer, Tanja; Hinterreiter, Jürgen; Weiss, Andreas J.; Davies, Jackie A.; Möstl, Christian; Amerstorfer, Ute V.; Reiss, Martin A.; Harrison, Richard A.
Abstract: Being able to accurately predict the arrival of coronal mass ejections (CMEs) at Earth has been a long‐standing problem in space weather research and operations. In this study, we use the ELlipse Evolution model based on Heliospheric Imager (ELEvoHI) to predict the arrival time and speed of 10 CME events that were observed by HI on the STEREO‐A spacecraft between 2010 and 2020. Additionally, we introduce a Python tool for downloading and preparing STEREO‐HI data, as well as tracking CMEs. In contrast to most previous studies, we use not only science data, which have a relatively high spatial and temporal resolution, but also lower‐quality beacon data, which are—in contrast to science data—provided in real‐time by the STEREO‐A spacecraft. We do not use data from the STEREO‐B spacecraft. We get a mean absolute error of 8.81 ± 3.18 hr/59 ± 31 km s −1 for arrival time/speed predictions using science data and 11.36 ± 8.69 hr/106 ± 61 km s −1 for beacon data. We find that using science data generally leads to more accurate predictions, but using beacon data with the ELEvoHI model is certainly a viable choice in the absence of higher resolution real‐time data. We propose that these differences could be minimized if not eliminated altogether if higher quality real‐time data were available, either by enhancing the quality of the already available data or coming from a new mission carrying a HI instrument on‐board. Plain Language Summary: Coronal mass ejections (CMEs) are large ejections of plasma and the accompanying magnetic field caused by magnetic activity on the Sun. If CMEs reach Earth, they interact with the planetary magnetic field. In doing so, CMEs can cause disturbances to power grids and other electrical infrastructure on our planet, inhibit radio transmissions and damage satellites, which is why it is important to have an accurate way of predicting the arrival of the phenomena. Our model uses data provided by the HI cameras on the STEREO spacecraft. These data are available in a lower quality in real‐time, that is, within a latency of about 5 min within being received at the ground station, or in a higher quality with a delay of around 3 days. Using real‐time data is important if we want to be able to predict the arrival of CMEs in a timely manner. In this study, we show that we can use the lower‐quality real‐time STEREO‐HI data to make accurate predictions of the arrival time of CMEs. Key Points: The viability of using the Ellipse Evolution Model based on Heliospheric Imager (ELEvoHI) model with lower‐quality real‐time data was studied The impact of variations between time‐elongation profiles on CME predictions caused by human error was evaluated We find that using real‐time data with ELEvoHI is possible, but coronal mass ejection prediction benefits significantly from improved data quality